International criminal tribunals : a normative defense a normative defense - May, Larry; Fyfe, Shannon (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2017)
"In the last two decades there has been a meteoric rise of international criminal tribunals and courts and also a strengthening chorus of critics against them. Today it is hard to find strong defenders of international criminal tribunals and courts. This book attempts such a defense against an array of critics. It offers a nuanced defense, accepting many criticisms but arguing that the idea of international criminal tribunals can be defended as providing the fairest way to deal with mass atrocity crimes ina global arena. Fairness and moral legitimacy will be at the heart of this defense. The authors take up the economic and political arguments that have been powerfully expressed, as well as arguments about sovereignty, punishment, responsibility, and evidence ... "--Page [i].
Legitimacy -- Sovereignty -- Punishment -- Responsibility -- Economics -- Politics -- Evidence -- Fairness -- Concluding remarks.
Includes bibliographical references and index.
Keywords: International criminal courts; International criminal courts; Internationale Strafgerichtsbarkeit